"We support unity in diversity, but politic is a privilege for my group": The paradoxical influence of national identification × religious identification in predicting unity in diversity and political orientations. (March 2022) - Putra, Idhamsyah Eka; Yustisia, Whinda; Osteen, Chad; Hudiyana, Joevarian; Meinarno, Eko A.
Abstract: A sense of belonging to a nation and, simultaneously, to a religious group is commonly found in a society where religion is considered to be important. Such is the case in Indonesia where high and low of these senses of belonging may affect intergroup perceptions and political orientation. In two studies of Muslim and non-Muslim' samples ( Ns = 1005, 236) conducted in Indonesia, we investigated the interaction effects of national identification with religious identification on unity in diversity and political orientations. Consistently in two studies, nationalists with less sense of belonging to a religious group showed a more open and equal political perspective toward others, regardless of their group backgrounds. On the other hand, even though nationalists with high religious identification showed a tendency to support unity in diversity and prosocial values (study 1), they were found to also adopt an exclusionary approach toward the double-minority group of Chinese Indonesians' involvement in politics and the economy (study 2). Further findings are discussed by considering how context and other religious elements may play a role of national identifications in intercultural relations. Data and materials availability: All data are available In the OSF: https://osf.io/h5avz/?view_only=65d9c30bdcf5450ea5ce78b5bd2e8446 .